Evaluation of Mechanical and Physical Properties of Timber Available in Nepal using Indian Standard - Duwadi , Ima Nath (International Journal on Engineering Technology, 2025)
In Nepal's construction sector, timber remains an indispensable material, forming the backbone of residential buildings, commercial structures, and cultural heritage sites. Yet the absence of standardized quality assessment protocols has resulted in unpredictable material performance, compromising structural integrity and safety. This study bridges this critical gap by systematically evaluating four predominant Nepalese timber species - Sal (Shorea robusta), Sisau (Dalbergia sissoo), Chir Pine (Pinus roxburghii), and Utis (Alnus nepalensis) - employing arduous testing methodologies outlined in Indian Standard IS 1708:1986. Through comprehensive laboratory analysis, we quantified key mechanical properties including modulus of rupture (MOR), modulus of elasticity (MOE), compressive and tensile strengths, alongside physical characteristics like density. Our results demonstrate Sal's superior structural capacity (MOR: 129.9 N/mm²; MOE: 13,959.7 N/mm²), validating its traditional use in critical load-bearing elements. Sisau exhibited exceptional surface hardness, confirming its suitability for high-traffic flooring, while the lighter Chir Pine and Utis showed promising characteristics for cost-effective, non-structural applications. This research provides the first standardized dataset for Nepalese timber species, offering a scientific basis for material selection that harmonizes traditional building knowledge with modern engineering requirements. The implementation of IS-based evaluation protocols presents a practical pathway for Nepal to establish much-needed quality benchmarks, enhance construction safety, and optimize the use of its valuable forest resources in an era of increasing seismic awareness and sustainability concerns.